PERBANDINGAN KARTU KREDIT DAN KARTU KREDIT BERBASIS SYARIAH DI INDONESIA - Zainul Arifin Yusuf (Al-Iqtishad: Jurnal Ilmu Ekonomi Syariah, 2011)
Apparently, even causing the pros and contra, the business of credit cards tempts most perpetrators of Islamic banks to makesharias’credit card. Sharia based credit cards have a number of differences than the conventional credit card. One of them is the basic law that refers to the Banking Law, as well as to the Islamic banking law, and the National Fatwa Council of Sharia. In addition, Islamic credit cards are credit cards that implement the wage system (ujrah). In the transaction, Islamic credit card users free of interest and penalties. Penalties only apply to customers who are in default, and the fine is not used as revenue for the bank, but it is distributed to the social fund